Comparative evaluation of pancreatic histopathology of rats treated with olanzapine, risperidone and streptozocin (Brazilian Journal of Pharmaceutical Sciences, 2018)
Olanzapine and risperidone are widely prescribed atypical antipsychotics used in the treatment of schizophrenia and various other psychiatric disorders. Both of these drugs have been extensively reported to cause Type 2 diabetes mellitus and pancreatitis, however, the mechanism of olanzapine and risperidone-induced toxicity has not been so far unveiled. We, therefore, compared the streptozocininduced pancreatic damage with that of pancreas isolated from olanzapine and risperidone treated rats. It was noticed that fibrotic growth, necrosis and derangement of the pancreatic islet cells caused by streptozocin were more pronounced than olanzapine and risperidone.